Anti-PD-L1 × anti-CD3 bispecific T-cell engager-armed T cells can overcome immunosuppression and redirect T cells to kill breast cancer cells expressing PD-L1 - Luangwattananun P. (2023)
T cell-based immunotherapy has transformed cancer treatment. Nonetheless, T cell antitumor activity can be inhibited by an immune checkpoint molecule expressed on cancer cells, program death ligand 1 (PD-L1), which interacts with the PD-1 on T cells. We generated αPD-L1 × αCD3 bispecific T-cell engager-armed T cells (BATs) to prevent PD-L1/PD-1 interaction and hence to redirect T cells to kill cancer cells. αPD-L1 × αCD3 bispecific T-cell engagers (BTEs) were produced from Chinese hamster ovary (CHO) cells to arm human primary T cells. Flow cytometry was used to investigate BTE binding to BATs. The cytotoxicity of BATs against PD-L1-expressing breast cancer (BC) cell lines was assessed in 2-dimensional (2D) and 3-dimensional (3D) culture models. The binding stability of BTE on BATs and their efficacy after cryopreservation were also examined. The CHO cell BTE expression yield was 3.34 mg/ml. The binding ability on T cells reached 91.02 ± 4.2 %. BATs specifically lysed PD-L1-expressing BC cells, with 56.4 ± 15.3 % HCC70 cells and 70.67 ± 15.6 % MDA-MB-231 cells lysed at a 10:1 effector-to-target ratio. BATs showed slight, nonsignificant lysis of PD-L1-negative BC cells, MCF-7, and T47D. Moreover, BATs significantly disrupted MDA-MB-231 3D spheroids expressing PD-L1 after 48 and 72 h of coculture. Cryopreserved BATs maintained BTE binding stability, cell viability, and anticancer activity, comparable to fresh BATs. αPD-L1 × αCD3 BATs induced the cytolysis of PD-L1-expressing BC cells in 2D and 3D coculture assays. BATs can be prepared and preserved, facilitating their use and transportation. This study demonstrates the potential of αPD-L1 × αCD3 BATs in treating cancers with positive PD-L1 expression.